Spatial distribution of Tuberculosis in the North of Minas Gerais State - Magalhães, Sandra Célia Muniz; Lima, Samuel do Carmo (Revista Cerrados, 2011)
The aim of this article is to discuss the spatial distribution of tuberculosis in the North Region of Minas Gerais State in 2010. The methodology used was bibliographic and documental research. Data of tuberculosis occurrences in the municipalities of the North of Minas Gerais were obtained from SINAN – Notification of Aggravation Information System. Tuberculosis, a disease closely related to the population precarious life conditions find in some Brazilian regions the ideal conditions for its spreading, once the prevention and control are not satisfactory. Risk factors such as people agglomeration allied to lack of basic sanitation system, insanitary housing, malnutrition and improper hygiene lead to the disease quick propagation. In the North of Minas Gerais the occurrence of tuberculosis is still high, with new cases emerging each year. Therefore, it is necessary to extend prevention and control actions in the areas of major occurrences of the disease, and the governmental organs responsible for this issue must be more efficient and active.